Juventude e cidadania na sulanca e a política do Projovem - Eufrasio, Marcelo Alves Pereira (2018)
This research has as main objective to investigate the public politics of schooling and qualification, particularly regarding the implementation of Projovem Urbano in the municipality of Caruaru-PE, a central region of Agreste Pernambucano, where, since the 1950s, the Pólo de Confecções. From a sociological point of view, the reality of the insertion of young people in the world of work was studied, being an aspect of the guarantee to the social citizenship, especially analyzing the challenges, impasses andstrategies of construction of a youthful protagonism.